Suicidality and Suicide Bombing Revisited: A Rejoinder to Merari. - Brym, RobertJ.; Araj, Bader (Studies in Conflict & Terrorism, 2012)
Ariel Merari purports to demonstrate a tendency on the part of suicide bombers to be motivated by depression and suicidal tendencies. However, he misconstrues the present authors' critique of his work and misinterprets their research. By clarifying both issues, this article seeks to substantiate three claims: (1) Merari's sampling procedure precludes generalization; (2) interviewer and contextual effects probably bias his findings; (3) evidence challenges his inferences.